Human ISWI chromatin-remodeling complexes sample nucleosomes via transient binding reactions and become immobilized at active sites - Erdel, Fabian; Schubert, Thomas; Marth, Caroline; Längst, Gernot; Rippe, Karsten (Proceedings of the National Academy of Sciences of the United States of America, 2010)
Chromatin remodeling complexes can translocate nucleosomes along the DNA in an ATP-dependent manner. Here, we studied autofluorescent protein constructs of the human ISWI family members Snf2H, Snf2L, the catalytically inactive Snf2L+13 splice variant, and the accessory Acf1 subunit in living human and mouse cells by fluorescence microscopy/spectroscopy. Except for Snf2L, which was not detected in the U2OS cell line, the endogenous ISWI proteins were abundant at nuclear concentrations between 0.14 and 0.83 μM. A protein interaction analysis showed the association of multimeric Snf2H and Acf1 into a heterotetramer or higher-order ACF complex. During the G1/2 cell cycle phase, Snf2H and Snf2L displayed average residence times <150 ms in the chromatin-bound state. The comparison of active and inactive Snf2H/Snf2L indicated that an immobilized fraction potentially involved in active chromatin remodeling comprised only 1-3%. This fraction was largely increased at replication foci in S phase or at DNA repair sites. To rationalize these findings we propose that ISWI remodelers operate via a “continuous sampling” mechanism: The propensity of nucleosomes to be translocated is continuously tested in transient binding reactions. Most of these encounters are unproductive and efficient remodeling requires an increased binding affinity to chromatin. Due to the relatively high intranuclear remodeler concentrations cellular response times for repositioning a given nucleosome were calculated to be in the range of tens of seconds to minutes.